Frequency upconversion properties of Tm3+ doped TeO2-ZnO glasses containing silver nanoparticles - de Assumpcao, Thiago A. A.; da Silva, Davinson M.; Camilo, Mauricio E. [UNESP]; Kassab, Luciana R. P. [UNESP]; Anderson, S.; de Araujo, Cid B.; Wetter, Niklaus U. (Elsevier B.V. Sa, 2012)
Frequency upconversion (UC) properties of Tm3+ doped TeO2-ZnO glasses containing silver nanoparticles (NPs) were investigated. Infrared-to-visible and infrared-to-infrared UC processes associated to the Tm3+ ions were studied by exciting the samples with a cw 1050 nm ytterbium laser. The luminescence intensity as a function of laser intensity was also measured using a pulsed 1047 nm Nd3+:YVO laser in order to determine the number of photons participating in the UC processes. Enhancement of the UC signals for samples heat-treated during various time intervals is attributed to the growth of the local field in the vicinity of the NPs. PL enhancement by one-order of magnitude was observed in the whole spectrum of the samples heat-treated during 48 h. on the other hand PL quenching was observed for the samples heat-treated more than 48 h. (c) 2011 Elsevier B.V. All rights reserved.
Keywords: Nanostructured materials; Rare-earth compounds; Optical properties; Luminescence; Localized surface plasmons; Frequency upconversion